2011
DOI: 10.2460/javma.239.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Surgical time and severity of postoperative pain in dogs undergoing laparoscopic ovariectomy with one, two, or three instrument cannulas

Abstract: Results suggested that laparoscopic ovariectomy with 2 instrument cannulas, rather than with 1, resulted in shorter surgical times without increasing severity of postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
153
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(162 citation statements)
references
References 14 publications
5
153
1
2
Order By: Relevance
“…221 Ovariohysterectomy and ovariectomy-There are many acceptable variations of the surgical procedures that can be used to sterilize female cats and dogs. 16,46,[197][198][199][200][201][202][203][204][205][206][207][208][209]211,212,[222][223][224][225] The particular surgical procedure and its details, including the length and location of the surgical incision and ligation techniques, will vary depending on the program, the veterinarian's preferences, and the individual patient's needs. In all cases, complete removal of both ovaries is required.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…221 Ovariohysterectomy and ovariectomy-There are many acceptable variations of the surgical procedures that can be used to sterilize female cats and dogs. 16,46,[197][198][199][200][201][202][203][204][205][206][207][208][209]211,212,[222][223][224][225] The particular surgical procedure and its details, including the length and location of the surgical incision and ligation techniques, will vary depending on the program, the veterinarian's preferences, and the individual patient's needs. In all cases, complete removal of both ovaries is required.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Interestingly, surgical time was not significantly different with the use of 2 or 3 cannulae (approximately 19 minutes total surgical time), and complication rates were not significantly different among the groups. 1 Conversely, a study comparing laparoscopic ovariectomy in dogs using a single or 2-portal technique showed no significant difference in total surgical time (approximately 20 minutes) between the 2 techniques. Factors significantly affecting surgical time included body condition score, ovarian ligament fat score, ovarian bleeding, and surgeon expertize.…”
Section: Introductionmentioning
confidence: 96%
“…6 In addition, in human and veterinary surgery, there has been interest in reducing the number and size of portals in endosurgery, in an attempt to reduce postoperative pain. 1,2,7 In a comparative study in dogs undergoing laparoscopic ovariectomy, the use of 2 cannulae significantly lower the postoperative pain score when compared with the use of 1 cannula or 3 cannulae. 1 However, the same study showed that reducing the number of portals might prolong surgical time.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations